Urbanization in the Republic of Kazakhstan : the growth of the cities and its relationship with the changes in the economy - Aubakirova, Tolkyn (2021)
Urbanization is playing an essential role in the economic and social development of the world. Kazakhstan has a relatively low rate of urbanization, and urban development can provide new opportunities to improve financial well-being. This study examines whether urbanization has a significant impact on the economic growth of the Republic of Kazakhstan. Panel data analysis is applied for annual data, including demographic and macroeconomic indicators from 17 regions of Kazakhstan for 2000-2019. Three versions of the empirical model (pooled model, fixed effect model, random effect model) with two independent variables are estimated. The Breusch-Pagan LM and Hausman tests are applied to check the most appropriate model for explaining the relationship of share of the urban population and economic growth. Model specification tests are resulted in choosing the random effect model as the most suitable in this study. Trends and patterns of urban development in Kazakhstan have been investigated, and empirical analysis proves the hypothesis that the higher the share of urban population is associated with the higher rates of Kazakhstan’s economic growth. The findings also reveal that the unemployment rate and economic growth have a strong correlation, which corresponds with published research findings. This thesis has a sufficient contribution in studying the impact of urbanization on the economic performance of Kazakhstan due to the lack of research about the relationship between urban population percentage and economic growth.